Neurogenic Thoracic Outlet Syndrome Associated with Cervical Rib - Millan, G (2013)
A true neurogenic thoracic outlet syndrome (TOS) associated with a cervical rib is considered extremely rare. The authors present their experience with 5 cases of true neurogenic TOS associated with a cervical rib. All patients were female and had a cervical rib confirmed radiographically pre-operatively. Average age was 34,8 years. Although all patients had been treated with several combinations of diverse drugs and a rehabilitation program before referral to surgery, all described their pain as intense and debilitating before surgical treatment. All patients had pre-operative electromyographic abnormalities. Patients were operated on via a supraclavicular approach and the cervical rib was resected. No intra-operative or postoperative complications were noted. Two years postoperatively, all patients mentioned improvement. However, only 2 were symptomless, and on no medication. In one patient there was significant improvement, and in the remaining 2 patients some residual pain persisted that had to be dealt with pharmacologically. All patients were able to resume their daily life activities. Recovery was poorer in the 2 patients that had been referred to surgery after a longer period of time since the beginning of symptoms.